1988
DOI: 10.1295/polymj.20.213
|View full text |Cite
|
Sign up to set email alerts
|

Radical Grafting from Carbon Black. Graft Polymerization of Vinyl Monomers Initiated by Peroxyester Groups Introduced onto Carbon Black Surface

Abstract: Carbon blacks having tert-butyl peroxyester groups (1, 2, and 3) were prepared by the reaction of acyl chloride CB-COO -t-Bu II 0 CB-O-C(CH2) 4 ~-OO-t-Bu 0 2 yH3 CB-y-(CH2)i-~-OO-t-Bu CN 0 3 groups on carbon black with tert-butyl hydroperoxide. The introduction of acyl chloride groups onto carbon black was achieved by three methods: (I) reaction of a carboxyl group with thionyl chloride, (2) reaction of a phenolic hydroxyl group with adipoyl chloride, and (3) reaction of thionyl chloride with a carboxyl group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 13 publications
1
37
0
2
Order By: Relevance
“…[7][8][9][10]35,36 During the polymerization in organic solvents, it was confirmed that the grafted polymer chains propagate from the surface radicals formed by the thermal decomposition of azo and peroxyester groups introduced onto the surface. Therefore, we designed the radical graft polymerization of vinyl monomers from silica nanoparticle surface initiated by azo and peroxycarbonate groups in a solventfree dry-system.…”
Section: Radical Grafting Of Vinyl Polymers Onto Silica Nanoparticle mentioning
confidence: 96%
See 2 more Smart Citations
“…[7][8][9][10]35,36 During the polymerization in organic solvents, it was confirmed that the grafted polymer chains propagate from the surface radicals formed by the thermal decomposition of azo and peroxyester groups introduced onto the surface. Therefore, we designed the radical graft polymerization of vinyl monomers from silica nanoparticle surface initiated by azo and peroxycarbonate groups in a solventfree dry-system.…”
Section: Radical Grafting Of Vinyl Polymers Onto Silica Nanoparticle mentioning
confidence: 96%
“…[4][5][6][7] This suggests that polymerization can be initiated by both surface radicals and fragment radicals formed by the thermal decomposition of the surface azo groups: the surface radicals produce surface-grafted polymer, but the fragment radicals produce ungrafted polymer, as shown in Scheme 4. It is thought that during the final stage of graft polymerization, the latter reaction proceeds preferentially, resulting in a decrease in grafting efficiency.…”
Section: Radical Graft Polymerization Initiated By Surface Azo Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsubokawa et al have reported that polymer radicals formed by the thermal decomposition of azo polymers 8 and peroxide polymers 9 are effectively trapped by polycondensed aromatic rings of the CB surface to give the corresponding polymer-grafted CB. Therefore, the grafting reaction of the CB surface with NR radicals formed by the thermal dissociation was examined in this paper.…”
Section: Grafting Of Nr Onto the Carbon Black Surfacementioning
confidence: 99%
“…The second is ''grafting from'' which involves surface initiation then subsequent polymer grew from the surface. Tsubokawa and co-workers [8][9][10] have reported some other methods to graft polymer by CB surface trapping polymer radicals which was formed by thermal decomposition of some polymers such as azo, peroxide polymer and so on.…”
mentioning
confidence: 99%